2017
DOI: 10.1177/0011128716686339
|View full text |Cite
|
Sign up to set email alerts
|

Community Policing: Least Effective Where Need Is Greatest

Abstract: Little is known about the level or impact of community policing in suburban and rural communities. We surveyed more than 1,300 cities and counties and asked city managers about social cohesion, collective efficacy, and community policing variables. We find no effect of community policing on perception of safety and a positive effect on community participation only in the metro core. For suburbs and rural areas, community policing is only related to youth services. Collective efficacy is positively associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 40 publications
1
23
0
4
Order By: Relevance
“…The effects of COP in larger jurisdictions are also somewhat tenuous. While a case study of a large Southern community by Lord, Kuhns, and Friday (2009) indicated that adoption of COP had no effect on citizen perceptions of police or fear of crime, Rukus et al (2018) found community policing had a positive effect on community participation in metro areas. Similarly, Zhao, Scheider, and Thurman (2002) found that COP funding was associated with significant reductions in violent crime in large cities.…”
Section: Disparities Between Large and Small Jurisdictionsmentioning
confidence: 94%
See 2 more Smart Citations
“…The effects of COP in larger jurisdictions are also somewhat tenuous. While a case study of a large Southern community by Lord, Kuhns, and Friday (2009) indicated that adoption of COP had no effect on citizen perceptions of police or fear of crime, Rukus et al (2018) found community policing had a positive effect on community participation in metro areas. Similarly, Zhao, Scheider, and Thurman (2002) found that COP funding was associated with significant reductions in violent crime in large cities.…”
Section: Disparities Between Large and Small Jurisdictionsmentioning
confidence: 94%
“…Regarding small jurisdictions, a study of five communities by Adams, Rohe, and Arcury (2005), for example, revealed that implementation of COP prompted lower levels of fear of crime and increased community attachment among residents. The findings of recent study by Rukus et al (2018), suggested that community policing was related to youth services in suburbs and rural areas. Similarly, a study of a single community by Brand and Birzer (2003) indicated that implementation of COP was associated with improved police services and resident perceptions of the police department, as well as reductions in crimea finding that stands in conflict to that of a similar case study conducted by Prine, Ballard, and Robinson (2001).…”
Section: Disparities Between Large and Small Jurisdictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, not all members of society perceive their police services as having legitimacy, even when the philosophy and components of CP are used (Rukus et al, 2018). In order to gauge Torontonians' perceptions of the TPS's legitimacy, the Toronto Police Services Board (TPSB) conducted a quantitative study in 2019 to measure community members' perception of the TPS's legitimacy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…High-crime and high-deprivation neighbourhoods have traditionally been made up of visible minorities in western countries, leading to outsider perceptions that the members of the community themselves are problematic (Drummond, 2018;Adedoyin et al, 2019). Community policing was not designed to create proactive partnerships between the police and one specific group, but rather to help all racial, ethnic, religious, and cultural groups that traditionally have or do not have a positive relationship with the police (Rukus et al, 2018). It allows all individuals in the community to acquire a sense of power and helps build a perception of police legitimacy and trust in the police service (Rukus et al, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%